Development of Biofortified Maize Hybrids through Marker-Assisted Stacking of β-Carotene Hydroxylase, Lycopene-ε-Cyclase and Opaque2 Genes - Zunjare, Rajkumar U.; Hossain, Firoz; Muthusamy, Vignesh; Baveja, Aanchal; Chauhan, Hema S.; Bhat, Jayant S.; Thirunavukkarasu, Nepolean; Saha, Supradip; Gupta, Hari S. (Frontiers in Plant Science, 2018)
Traditional yellow maize though contains high kernel carotenoids, the concentration of provitamin A (proA) is quite low (<2 μg/g), compared to recommended level (15 μg/g). It also possesses poor endosperm protein quality due to low concentration of lysine and tryptophan. Natural variant of crtRB1 (β-carotene hydroxylase) and lcyE (lycopene-ε-cyclase) cause significant enhancement of proA concentration, while recessive allele, opaque2 (o2) enhances the level of these amino acids. Development of biofortified maize enriched in proA, lysine and tryptophan thus holds significance in alleviation of micronutrient malnutrition. In the present study, marker-assisted stacking of crtRB1, lcyE and o2 was undertaken in the genetic background of four maize hybrids (HQPM1, HQPM4, HQPM5 and HQPM7) popularly grown in India. HP704-22 and HP704-23 were used as donors, while four elite QPM parents viz., HKI161, HKI163, HKI193-1 and HKI193-2 were used as recipients. CrtRB1 showed severe segregation distortion, while lcyE segregated as per the expectation. Recovery of recurrent parent genome among selected backcross progenies ranged from 89 to 93%. Introgressed progenies possessed high concentration of proA (7.38 to 13.59 μg/g), compared to 1.65 to 2.04 μg/g in the recurrent parents. The reconstituted hybrids showed an average of 4.5-fold increase in proA with a range of 9.25 to 12.88 μg/g, compared to original hybrids (2.14 to 2.48 μg/g). Similar plant-, ear- and grain- characteristics of improved versions of both inbreds and hybrids were observed when evaluated with their respective original versions. Mean lysine (0.334%) and tryptophan (0.080%) of the improved hybrids were at par with the original versions (lysine: 0.340%, tryptophan: 0.083%). Improved hybrids also possessed similar grain yield potential (6301 to 8545 kg/ha) with their original versions (6135 to 8479 kg/ha) evaluated at two locations. This is the first study of staking crtRB1-, lcyE- and o2-, favourable alleles in single genetic background. The improved inbreds can be effectively used as potential donor for independent and/or simultaneous introgression of crtRB1, lcyE and o2 in the future breeding programme. These biofortified maize hybrids, rich in proA, lysine and tryptophan will hold great promise for nutritional security.